MAKNA AKUNTANSI PERTANGGUNGJAWABAN YANG MELAMPAUI - Hanif Hanif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
The concept of responsibility accounting accompanies the concept of responsibility center which means that any authority given to a manager over a business unit must be accounted for by that authority, especially the authority in achieving financial targets, both revenue and expenses. The concept of responsibility center and responsibility accounting are management tools to ensure that the entrusted manager truly upholds the trust by exercising the given authority and must dare to take responsibility for that authority in the future. This concept also emphasizes that a manager cannot be held responsible by his superiors for more than the authority given to him. More than that, this concept aims not to let in the management of the organization, managers throw responsibilities at each other or